2004
DOI: 10.1002/jbm.a.30073
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer surface roughness increases select osteoblast adhesion on carbon nanofiber compacts

Abstract: Carbon nanofibers have exceptional theoretical mechanical properties (such as low weight-to-strength ratios) that, along with possessing nanoscale fiber dimensions similar to crystalline hydroxyapatite found in bone, suggest strong possibilities for use as an orthopedic/dental implant material. To determine, for the first time, cytocompatibility properties pertinent for bone prosthetic applications, osteoblast (bone-forming cells), fibroblast (cells contributing to callus formation and fibrous encapsulation ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(180 citation statements)
references
References 20 publications
8
166
0
6
Order By: Relevance
“…The adhesion of living cells was enhanced by the nanostructured TNT layer, as evidenced by the rapid spreading curves recorded by OWLS and the increased resistance to hydromechanical removal (by washing). The enhancement of cell adhesion is in line with the general observations of cell adhesion being enhanced by rough substrata [65][66][67]. We can exclude any effects of electrostatic interactions between protein and substratum, because at the ionic strength of the medium we used the electrostatic interactions are negligible in comparison with the Lewis acid/base interactions [64].…”
Section: Chemical States and The Origin Of Adsorption And Adhesion Ensupporting
confidence: 81%
“…The adhesion of living cells was enhanced by the nanostructured TNT layer, as evidenced by the rapid spreading curves recorded by OWLS and the increased resistance to hydromechanical removal (by washing). The enhancement of cell adhesion is in line with the general observations of cell adhesion being enhanced by rough substrata [65][66][67]. We can exclude any effects of electrostatic interactions between protein and substratum, because at the ionic strength of the medium we used the electrostatic interactions are negligible in comparison with the Lewis acid/base interactions [64].…”
Section: Chemical States and The Origin Of Adsorption And Adhesion Ensupporting
confidence: 81%
“…Price et al have made composites of ceramics and carbon nanofibers and reported that the finer surface of the specimens increased the attachment area of osteoblasts, and the number of attached cells increased with an increase in the addition of carbon nanofibers [44,45]. Thus, various arguments have been made regarding the influence of ceramic surface conditions on cell attachment.…”
Section: Discussionmentioning
confidence: 99%
“…e adsorption of select proteins can in this manner guide the adhesion of cells on the implant material surface, among other capabilities. Various investigations have exhibited improved cell adhesion and multiplication on nanostructured surfaces, with various potential tissue applications, including applications in the bladder, bone, vasculature, and nervous system [32][33][34]. A prior study suggested that TNSs on titanium surfaces facilitate the regulation of osteoblastic differentiation of bone marrow cells and enhance mineralization.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%